Electron Density‐Change in Semiconductor by Ion‐Adsorption at Solid–Liquid Interface. Issue 10 (4th February 2021) - Lee, Won Hyung; Yoon, Sun Geun; Jin, Huding; Yoo, Jeeyoung; Han, Junghyup; Cho, Yong Hyun; Kim, Youn Sang
Abstract: The change in electrical properties of electrodes by adsorption or desorption at interfaces is a well‐known phenomenon required for signal production in electrically transduced sensing technologies. Furthermore, in terms of electrolyte–insulator–semiconductor (EIS) structure, several studies of energy conversion techniques focused on ion‐adsorption at the solid–liquid interface have suggested that the electric signal is generated by ionovoltaic phenomena. However, finding substantial clues for the ion‐adsorption phenomena in the EIS structure is still a difficult task because direct evidence for carrier accumulation in semiconductors by Coulomb interactions is insufficient. Here, a sophisticated Hall measurement system is demonstrated to quantitatively analyze accumulated electron density‐change inside the semiconductor depending on the ion‐adsorption at the solid–liquid interface. Also, an enhanced EIS‐structured device is designed in an aqueous‐soaked system that works with the ionovoltaic principle to monitor the ion‐dynamics in liquid electrolyte media, interestingly confirming ion‐concentration dependence and ion‐specificity by generated peak voltages. This newly introduced peculiar method contributes to an in‐depth understanding of the ionovoltaic phenomena in terms of carrier actions in the semiconductors and ionic behaviors in the aqueous‐bulk phases, providing informative analysis about interfacial adsorptions that can expand the scope of ion‐sensing platforms. Abstract : Water‐immersed Hall measurements are proposed to find direct evidence of ion‐adsorption at the solid–liquid interface. Electron density‐change by diffusion‐driven ion dynamics occurs in a fully liquid‐submerged device designed to monitor ion‐specific dynamics in aqueous bulk phases. The ion‐concentration gradient and diffusion coefficient of mobile ions are correlated with ion‐adsorption rate, causing electric signal variations in the semiconductor.